2023
DOI: 10.3389/fnmol.2023.1123708
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based predictive models and drug prediction for schizophrenia in multiple programmed cell death patterns

Abstract: BackgroundSchizophrenia (SC) is one of the most common mental illnesses. However, the underlying genes that cause it and its effective treatments are unknown. Programmed cell death (PCD) is associated with many immune diseases and plays an important role in schizophrenia, which may be a diagnostic indicator of the disease.MethodsTwo groups as training and validation groups were chosen for schizophrenia datasets from the Gene Expression Omnibus Database (GEO). Furthermore, the PCD-related genes of the 12 patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Multiple studies have demonstrated that neuronal cell death often transpires due to ferroptosis ( Ren et al, 2023 ; Wang D. et al, 2023 ). In our previous research, we have identified connections between psycho-neuro-degeneration and various factors, including programmed cell death (PCD), mitochondrial function, vesicular transport, and cuproptosis ( Feng and Shen, 2023 ; Feng et al, 2023 ; Shen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that neuronal cell death often transpires due to ferroptosis ( Ren et al, 2023 ; Wang D. et al, 2023 ). In our previous research, we have identified connections between psycho-neuro-degeneration and various factors, including programmed cell death (PCD), mitochondrial function, vesicular transport, and cuproptosis ( Feng and Shen, 2023 ; Feng et al, 2023 ; Shen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a RF approach, they found 103 additional gene interactions were expanded to schizophrenia-associated networks, which were shared amongst both the dorsolateral prefrontal cortex and amygdala regions [51]. Another study by Feng and Shen used neural networks using programmed cell-death-related genes as features and found 10 candidate hub genes (DPF2, ATG7, GSK3A, TFDP2, ACVR1, CX3CR1, AP4M1, DEPDC5, NR4A2, and IKBKB) [52]. Finally, a study on fresh frozen post-mortem brain tissue aimed to identify DNA methylation patterns specific to schizophrenia patients.…”
Section: Identifying Features Of Schizophreniamentioning
confidence: 99%